Community and familial dynamics influencing risk behavior for HIV acquisition among adolescent girls and young women in Uganda: Qualitative analysis using Protective Motivation Theory. - Rose Apondi; Hilde Bastiaens; Christiana Nöstlinger; Jennifer Galbraith; Tiffiany M Aholou; Amy Medley; Rhoda K Wanyenze; Anna C Awor; David M Serwadda; George Aluzimbi; Juliet Cheptoris; Moses Ogwal; et al. (PLoS ONE)
Background In Uganda, adolescent girls', and young women's (AGYW-15-24 years) current HIV prevalence is fourfold compared with their male counterparts due to compounded social, economic, and environmental factors. Using the Protective Motivation Theory (PMT), we explored HIV-acquisition risk sources and perceived protective factors from AGYW and caregivers' perspective. Materials and methods During 2018, we conducted a qualitative study guided by PMT to explore factors influencing HIV acquisition among AGYW. We purposively sampled two groups of key informants, AGYW at high-risk for HIV acquisition (uninfected) and AGYW living with HIV, varied by age and place of residence (urban/rural). We conducted 34 focus group discussions with AGYW, nine with AGYW parents, and 25 key informant interviews. Data were analyzed using the framework method based on the PMT and developed from participants' narratives. Results AGYW were knowledgeable about HIV, HIV acquisition risk factors, and HIV prevention interventions. Nonetheless, few AGYW knew about pre-exposure prophylaxis (PrEP). Imbalance in power relations between the genders explained inability of AGYW making safe healthy decisions, with social norms giving men power over women. Parents modelling positively influenced HIV risk behavior. Many AGYW viewed staying in school a protective factor both while at school and further for life. AGYW identified alcohol use, desire for material possessions, discounting HIV disease severity, social norms, and poverty as barriers to engaging in self-protective behaviors. Several AGYW believed that access to AGYW-focused programs would facilitate healthy sex-positive, protective behaviors. Discussion While PMT focuses on individual factors confirmed by our findings, we found HIV risk behavior to be influenced by complex contextual factors including poverty, gender inequality and cultural norms. Distinct HIV risk factors among AGYW require policy and comprehensive targeted interventions addressing violence, alcohol consumption, increased economic opportunities, educational opportunities, safe-sex practices, and PrEP scale-up which may prevent HIV in AGYW and facilitate HIV epidemic control.